Shaping the Workforce of Tomorrow : A Comprehensive Review of Competence-Based Learning for Employability Enhancement - Rahmaningtyas, Wisudani; Joyoatmojo, Soetarno; Kristiani, Kristiani; Murwaningsih, Tri; Noviani, Leni (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to provide a comprehensive overview of competence-based learning in improving future employability skills and explain the basic concepts, principles, and the relevance of this approach in addressing rapid changes in the workplace. The research method used is a literature review with qualitative based on searching and analyzing relevant scientific articles, books, and publications related to competence-based learning and employability skills. The search was conducted through electronic academic databases such as Emerald, Scopus, Elsevier, Web of Science, ScienceDirect, Sinta, and ResearchGate using keywords "competence," "competence-based learning," and "employability." Data analysis used interactive model analysis by collecting articles with similar topics, then reducing and drawing conclusions. The results of this study indicate that emphasizing the importance of competence-based learning in shaping a future workforce that is ready to face global challenges. Policy recommendations and practical advice are directed towards education implementers to integrate this approach into the education and training system. By adopting competence-based learning, it can prepare a resilient and skilled workforce capable of quickly adapting to changes in the job market.